Arid3c identifies an uncharacterized subpopulation of V2 interneurons during embryonic spinal cord development - Renaux, Estelle; Baudouin, Charlotte; Schakman, Olivier; Gay, Ondine; Martin, Manon; Marchese, Damien; Achouri, Younès; Rezsohazy, René; Gofflot, Françoise; Clotman, Frédéric (Frontiers in Cellular Neuroscience, 2024)
Motor activity is organized by neuronal networks composed of motor neurons and of a wide variety of pre-motor interneuron populations located in the brainstem and in the spinal cord. Differential expression and single-cell RNA sequencing studies recently unveiled that these populations subdivide into multiple subsets. However, some interneuron subsets have not been described yet, and the mechanisms contributing to this neuronal diversification have only been partly deciphered. In this study, we aimed at identifying additional markers to further describe the diversity of spinal V2 interneuron populations. Here, we compared the transcriptome of V2 interneurons with that of the other cells of the embryonic spinal cord and extracted a list of genes enriched in V2 interneurons, including Arid3c. Arid3c identifies an uncharacterized subset of V2 that partially overlaps with V2c interneurons. These two populations are characterized by the production of Onecut factors and Sox2, suggesting that they could represent a single functional V2 unit. Furthermore, we show that overexpression or inactivation of Arid3c does not alter V2 production, but its absence results in minor defects in locomotor execution, suggesting a possible function in subtle aspects of spinal locomotor circuit formation.